New Frontiers for Article 19(1) TEU: A Comment on Joined Cases C-554/21, C-622/21 and C-727/21 Hann-Invest - Nika Bačić Selanec; Davor Petrić (Croatian Yearbook of European Law and Policy)
Hann-Invest is the first case of the Court of Justice of the EU assessing the state of the rule of law and independence of the judiciary in Croatia, and the most important judgment for the country since its accession to the European Union. But the judgment also has profound transversal relevance for future developments in EU law. In Hann-Invest, the Court of Justice ruled that Article 19(1) TEU precludes the Croatian judicial mechanism from ensuring the uniform application of the national case law. The disputed mechanism authorised the involvement of the national courts’ judicial administration into the decision-making process of the competent judicial panels, in particular through the so-called ‘registrations judges’ who were assigned to monitor the coherence of decisions leaving the court’s docket and by referring problematic cases to the collective decision-making of the judicial plenums in extra-procedural meetings. By declaring such an organisation of the national judiciary incompatible with EU law, the Court of Justice has established the initial doctrinal framework of ‘internal judicial independence’ under Article 19(1) TEU – further developing and reaffirming the value of the individual autonomy of national judges which, in its essence, has been considered central to the effective application of Union law since the Simmenthal ruling. Moreover, with Hann-Invest, the Court has set the trajectory of its future jurisprudence on Article 19(1) TEU beyond the scenarios of rule-of-law ‘backsliding’, potentially signalling the beginning of intense involvement with standard modes of operation of national judiciaries, which were until recently considered outside the EU’s reach.